Animal migrations and parasitism: reciprocal effects within a unified framework. (4th March 2021) - Poulin, Robert; de Angeli Dutra, Daniela
ABSTRACT: Migrations, i.e. the recurring, roundtrip movement of animals between distant and distinct habitats, occur among diverse metazoan taxa. Although traditionally linked to avoidance of food shortages, predators or harsh abiotic conditions, there is increasing evidence that parasites may have played a role in the evolution of migration. On the one hand, selective pressures from parasites can favour migratory strategies that allow either avoidance of infections or recovery from them. On the other hand, infected animals incur physiological costs that may limit their migratory abilities, affecting their speed, the timing of their departure or arrival, and/or their condition upon reaching their destination. During migration, reduced immunocompetence as well as exposure to different external conditions and parasite infective stages can influence infection dynamics. Here, we first explore whether parasites represent extra costs for their hosts during migration. We then review how infection dynamics and infection risk are affected by host migration, thereby considering parasites as both causes and consequences of migration. We also evaluate the comparative evidence testing the hypothesis that migratory species harbour a richer parasite fauna than their closest free‐living relatives, finding general support for the hypothesis. Then we consider the implications of host migratory behaviour for parasite ecology and evolution, which have received much less attention. Parasites of migratory hosts may achieve much greater spatial dispersal than those of non‐migratory hosts, expanding their geographical range, and providing more opportunities for host‐switching. Exploiting migratory hosts also exerts pressures on the parasite to adapt its phenology and life‐cycle duration, including the timing of major developmental, reproduction and transmission events. Natural selection may even favour parasites that manipulate their host's migratory strategy in ways that can enhance parasite transmission. Finally, we propose a simple integrated framework based on eco‐evolutionary feedbacks to consider the reciprocal selection pressures acting on migratory hosts and their parasites. Host migratory strategies and parasite traits evolve in tandem, each acting on the other along two‐way causal paths and feedback loops. Their likely adjustments to predicted climate change will be understood best from this coevolutionary perspective.